Is there an association between oocyte number and embryo quality? A systematic review and meta-analysis. Issue 5 (November 2019) - Vermey, Belinda G.; Chua, Su Jen; Zafarmand, Mohammad Hadi; Wang, Rui; Longobardi, Salvatore; Cottell, Evelyn; Beckers, Francois; Mol, Ben W.; Venetis, Christos A.; D'Hooghe, Thomas
Highlights: Positive association between oocytes retrieved and number of top/good quality embryos Pairwise comparisons of three categories of oocyte number corroborate this result Similar associations seen for MII oocytes, 2PN oocytes and euploid embryos Abstract: This systematic review and meta-analysis determined the association between aspirated after ovarian stimulation and top/good quality embryos obtained in women undergoing ovarian stimulation for IVF/intracytoplasmic sperm injection (ICSI). MEDLINE, EMBASE, Scopus, CINAHL and Web of Science were searched for English-language publications on top/good-quality embryos at cleavage (day 2/3) and/or blastocyst (day 5/6) developmental stages, up to 18 November 2017. Twenty-eight studies (three prospective and 25 retrospective) reporting data on 291, 752 assisted reproductive technology (ART) cycles were considered eligible. We confirmed a strong positive association between oocytes retrieved and top/good-quality day 2/3 embryos (weighted correlation coefficient [ r w ] = 0.791), day 5/6 embryos ( r w  = 0.901), metaphase II oocytes ( r w  = 0.988), oocytes exhibiting two pronuclei ( r w  = 0.987) and euploid embryos ( r w  = 0.851); P  < 0.001 for all correlations (evaluated in subsets of the 17 studies). Data from 5657 cycles showed that the group with the most oocytes aspirated had the most top/good-quality day 2/3 embryos (pooled standardized mean differences (high [>15] versus low [<4] 1.91, 95% confidence interval [CI] 1.05–2.77, P  < 0.0001; high versus medium [4–15] 1.15, 95% CI 0.74–1.55, P  < 0.0001; medium versus low 1.41, 95% CI 0.79–2.03, P  < 0.0001). Individual participant meta-analysis would enable accurate determination of these associations and other outcomes.